Evaluation of Sensitivity of Commonly used Antibiotics in Staphylococcus Epidermidis Clinical Isolates from Assir Region, Saudi Arabia (Global Journal of Medical Research, 2014)
Background: Multidrugs resistance is an emerging health problem that ultimately will lead to vanishing of effective medicine against infections including Staphylococcus epidermidis infections. Aim: This a prospective hospital base study of 58 Staphylococcus epidermidis clinical isolates in Assir region aim at evaluating the sensitivity profile of commonly used antibiotic during the period of March 2011-Sep. 2011. Materials and Methods: Bacteriology procedures ; staining, culture, catalase, coagulase and antibiotics sensitivity test using diffusion disc test, minimum inhibitory concentration (MIC) and molecular (PCR) for confirmation of Staphylococcal species and detection of the Mec A gene.
Keywords: staphylococcus epidermidis; coagulasenegative staphylococci (CoNS); antimicrobial resistance (AMR); nosocomial infections; diabetes